Knowledge utopias: An epistemological perspective on the convergence of museums, libraries and archives - Helena Robinson (Museum & Society, 2014)
Convergence of museums, libraries and archives is a trend that has manifested itself internationally within the last decade. Its incorporation into government cultural policies has led to significant investment and the formation of new institutions in a number of countries, while provoking discussion across the library, archives and museum sectors. Improved knowledge acquisition for users of collections is often cited as justification for convergence. However, while the creation of knowledge in museum, library or archive settings has been explored in a range of scholarship, the fundamental concept of ‘knowledge’ and its dissemination has not been comprehensively discussed in regard to convergence of these institutions. In response, this paper examines information, knowledge and epistemology in the context of convergence and challenges the legitimacy of the claim that convergence will deliver greater knowledge to collection users.